2010
DOI: 10.4067/s0718-16202010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Generalized composite interval mapping offers improved efficiency in the analysis of loci influencing non-normal continuous traits

Abstract: In genetic studies, most Quantitative Trait Loci (QTL) mapping methods presuppose that the continuous trait of interest follows a normal (Gaussian) distribution. However, many economically important traits of agricultural crops have a non-normal distribution. Composite interval mapping (CIM) has been successfully applied to the detection of QTL in animal and plant breeding. In this study we report a generalized CIM (GCIM) method that permits QTL analysis of non-normally distributed variables. GCIM was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…ized Linear Model under the GENMOD procedure (SAS ™ ) was used with a logarithmic link function (Myers et al, 2002;Mora et al, 2010).…”
Section: Multiplication Phasementioning
confidence: 99%
See 1 more Smart Citation
“…ized Linear Model under the GENMOD procedure (SAS ™ ) was used with a logarithmic link function (Myers et al, 2002;Mora et al, 2010).…”
Section: Multiplication Phasementioning
confidence: 99%
“…With Amaryllis species, low contamination rates of the explants were achieved with different concentrations of PPM (Smith et al, 1999). With R. bifida, Rodrigo et al (2006) found that the seeds treated with PPM were aseptic and had low levels of contamination, with no effect of PPM on later development or morphology.ized Linear Model under the GENMOD procedure (SAS ™ ) was used with a logarithmic link function (Myers et al, 2002;Mora et al, 2010). …”
mentioning
confidence: 99%